2009
DOI: 10.1128/aac.00782-08
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Observational Study of the Impact of VIM-1 Metallo-β-Lactamase on the Outcome of Patients with Klebsiella pneumoniae Bloodstream Infections

Abstract: VIM-1-producing Klebsiella pneumoniae (VPKP) is an emerging pathogen. A prospective observational study was conducted to evaluate the importance of VIM production on outcome of patients with K. pneumoniae bloodstream infections (BSIs). Consecutive patients with K. pneumoniae BSIs were identified and followed up until patient discharge or death. A total of 162 patients were included in the analysis; 67 (41.4%) were infected with VPKP, and 95 were infected with non-VPKP. Fourteen of the patients infected with VP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
201
0
11

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(214 citation statements)
references
References 31 publications
2
201
0
11
Order By: Relevance
“…Ben-David et al demonstrated ineffective antimicrobial therapy in all patients with CRKP and CSKP BSI (88% vs. 21%) associated with increased mortality [11]. Daikos et al also suggested that the effect of carbapenem resistance on mortality was probably mediated by the failure to provide effective antimicrobial therapy in patients with CRKP or CSKP infection (68% vs. 32%; OR 2.27, 95% CI 0.91-5.64) [12]. Although one study showed that tigecycline treatment appeared to be suitable for BSI caused by carbapenem-resistant Gramnegative bacteria [13], our study suggested that tigecycline could be associated with 100-fold risk of acquiring CRKP.…”
Section: Discussionmentioning
confidence: 99%
“…Ben-David et al demonstrated ineffective antimicrobial therapy in all patients with CRKP and CSKP BSI (88% vs. 21%) associated with increased mortality [11]. Daikos et al also suggested that the effect of carbapenem resistance on mortality was probably mediated by the failure to provide effective antimicrobial therapy in patients with CRKP or CSKP infection (68% vs. 32%; OR 2.27, 95% CI 0.91-5.64) [12]. Although one study showed that tigecycline treatment appeared to be suitable for BSI caused by carbapenem-resistant Gramnegative bacteria [13], our study suggested that tigecycline could be associated with 100-fold risk of acquiring CRKP.…”
Section: Discussionmentioning
confidence: 99%
“…18 In general, however, clinical data on the treatment of carbapenem-resistant Enterobacteriaceae infections are very limited and consist mainly of small case-series and brief reports. [18][19][20][21][22][23][24][25] Treatment options against infections due to MDR Gram-negative rods in leukemic and HSCT patients are summarized in Table 2.…”
Section: Resistant Gram-negative Rodsmentioning
confidence: 99%
“…Carbapenems may be a reasonable treatment option against carbapenemaseproducing K. pneumoniae provided that: (i) the carbapenem MIC for the infecting organism is ≤4 mg/L; (ii) a high-dose prolonged-infusion regimen is administered to drive the pharmacokinetic/ pharmacodynamic profile to acceptable exposures; and (iii) this class of agent is administered in combination with another active compound. 21 The caveat is that many carbapenemase producers are more substantially resistant, precluding such strategies.…”
Section: Combination Therapy In Infections Due To Resistant Gram-negamentioning
confidence: 99%
See 1 more Smart Citation
“…10 For clinicians and antimicrobial pharmacists, CPE pose a major challenge at the bedside as they significantly limit antimicrobial prescribing. 11 Morbidity and mortality are both increased in CPE infections, particularly bloodstream and respiratory infections, 12 with mortality rates ranging from 38-57%, 9 and poor outcomes in survivors, [13][14][15] emphasizing the need for commencement of timely targeted antimicrobial therapy to increase patient survival.…”
Section: Introductionmentioning
confidence: 99%